BUILDING FAMILY FINANCIAL INDEPENDENCE IN THE DIGITAL ERA - Nurlaila, Nurlaila; Husen, Irmawati A.; Husen, Zulaiha . (PT. Jurnal Center Indonesia Publisher, 2025)
The development of digital technology brings both challenges and opportunities for families in managing household finances. Low financial literacy and limited use of technology have caused some families to struggle in achieving financial independence. This community service activity aims to enhance family financial independence through socialization, digital financial literacy training, and technology-based business mentoring. The implementation methods include problem identification, delivery of financial literacy materials, practical use of digital financial applications, and online entrepreneurship assistance. The results show an increase in families’ knowledge of budgeting, saving, and utilizing digital platforms to generate additional income. Thus, this program contributes to the creation of more financially independent families in the digital era.